β-Hydroxybutyrate Oxidation in Exercise Is Impaired by Low-Carbohydrate and High-Fat Availability - David J. Dearlove; David Holdsworth; Tom Kirk; Leanne Hodson; Evelina Charidemou; Eline Kvalheim; Brianna Stubbs; Andrew Beevers; Julian L. Griffin; Rhys Evans; Jeremy Robertson; Kieran Clarke; et al. (Frontiers in Medicine, 2021)
Purpose: In this study, we determined ketone oxidation rates in athletes under metabolic conditions of high and low carbohydrate (CHO) and fat availability.Methods: Six healthy male athletes completed 1 h of bicycle ergometer exercise at 75% maximal power (WMax) on three occasions. Prior to exercise, participants consumed 573 mg·kg bw−1 of a ketone ester (KE) containing a 13C label. To manipulate CHO availability, athletes undertook glycogen depleting exercise followed by isocaloric high-CHO or very-low-CHO diets. To manipulate fat availability, participants were given a continuous infusion of lipid during two visits. Using stable isotope methodology, β-hydroxybutyrate (βHB) oxidation rates were therefore investigated under the following metabolic conditions: (i) high CHO + normal fat (KE+CHO); (ii) high CHO + high fat KE+CHO+FAT); and (iii) low CHO + high fat (KE+FAT).Results: Pre-exercise intramuscular glycogen (IMGLY) was approximately halved in the KE+FAT vs. KE+CHO and KE+CHO+FAT conditions (both p < 0.05). Blood free fatty acids (FFA) and intramuscular long-chain acylcarnitines were significantly greater in the KE+FAT vs. other conditions and in the KE+CHO+FAT vs. KE+CHO conditions before exercise. Following ingestion of the 13C labeled KE, blood βHB levels increased to ≈4.5 mM before exercise in all conditions. βHB oxidation was modestly greater in the KE+CHO vs. KE+FAT conditions (mean diff. = 0.09 g·min−1, p = 0.03; d = 0.3), tended to be greater in the KE+CHO+FAT vs. KE+FAT conditions (mean diff. = 0.07 g·min−1; p = 0.1; d = 0.3) and were the same in the KE+CHO vs. KE+CHO+FAT conditions (p < 0.05; d < 0.1). A moderate positive correlation between pre-exercise IMGLY and βHB oxidation rates during exercise was present (p = 0.04; r = 0.5). Post-exercise intramuscular βHB abundance was markedly elevated in the KE+FAT vs. KE+CHO and KE+CHO+FAT conditions (both, p < 0.001; d = 2.3).Conclusion: βHB oxidation rates during exercise are modestly impaired by low CHO availability, independent of circulating βHB levels.